СКРИНИНГОВЫЕ МЕТОДЫ ВЫЯВЛЕНИЯ ФИБРОЗА ПЕЧЕНИ - С. С. Вялов (Архивъ внутренней медицины)
The article presents current data on the diagnosis methods of liver diseases. Recommendations on the management of patients with pathology of the hepatic system on the detection of disease are given. The possibility of using different diagnostic techniques, including ultrasound, serum markers, and histological studies are investigated. The choice of diagnosis method is discussed.